2020
DOI: 10.1101/2020.06.19.20136028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted Proteomics of Right Heart Adaptation to Pulmonary Arterial Hypertension

Abstract: Rationale: No prior proteomic screening study has centered on the right ventricle (RV) in pulmonary arterial hypertension (PAH). Objectives: To identify the circulating proteomic profile associated with right heart maladaptive phenotype (RHMP) in PAH. Methods: Plasma proteomic profiling was performed using multiplex immunoassay in 121 PAH patients (discovery cohort from 2008-2011) and 76 (validation cohort from 2012-2014). The association between proteomic markers and RHMP (defined by the Mayo right heart scor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Candidate circulating biomarkers reported include those related to heart failure (uric acid, bilirubin, GDF15, hepatocyte growth factor, etc. ), [53][54][55][56] markers of inflammation (various cytokines and chemokines, c-reactive protein, soluble CD40 ligand, osteopontin, etc. ), [57][58][59][60][61] growth factors (VEGF, PDGF, TGF-beta, etc.…”
Section: Evaluating Biomarkers Of Disease Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Candidate circulating biomarkers reported include those related to heart failure (uric acid, bilirubin, GDF15, hepatocyte growth factor, etc. ), [53][54][55][56] markers of inflammation (various cytokines and chemokines, c-reactive protein, soluble CD40 ligand, osteopontin, etc. ), [57][58][59][60][61] growth factors (VEGF, PDGF, TGF-beta, etc.…”
Section: Evaluating Biomarkers Of Disease Activitymentioning
confidence: 99%
“…Other circulating biomarkers of RV maladaptation have also been recently reported in PAH. 55,56 Functional validation studies are warranted to elucidate the specific role of these markers in pathogenesis, as this could translate to novel RV-directed treatment targets in PAH. In another healthy population-based cohort, Dr. Synn showed that an automated CT measure of pulmonary vascular pruning, the BV5/TBV ratio, can detect early vascular remodeling that correlates with adverse changes in RV morphology and function.…”
Section: Summary and Future Directionsmentioning
confidence: 99%